The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1681/asn.2014080750
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Dynamics by Dynamin-Related Protein-1 in Acute Cardiorenal Syndrome

Abstract: Experimental evidence has clarified distant organ dysfunctions induced by AKI. Crosstalk between the kidney and heart, which has been recognized recently as cardiorenal syndrome, appears to have an important role in clinical settings, but the mechanisms by which AKI causes cardiac injury remain poorly understood. Both the kidney and heart are highly energy-demanding organs that are rich in mitochondria. Therefore, we investigated the role of mitochondrial dynamics in kidney-heart organ crosstalk. Renal ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 44 publications
(46 reference statements)
11
87
1
1
Order By: Relevance
“…Indeed, hydroxylamine derivatives, which activate optic atrophy-1 and promote the fusion of inner mitochondrial membranes, ameliorated lung damage in a murine model of pulmonary arterial hypertension [51]. Recently, treatment with a drug that prevents activation of the mitochondrial fission marker dynamin related protein (DRP)-1 ameliorated vascular remodeling and inflammation in spontaneously hypertensive rats [52], in accordance with previous observations in cardiomyocytes subjected to renal [53] and cardiac [54] reperfusion injury.…”
Section: Mechanisms Of Mitoprotectionsupporting
confidence: 75%
“…Indeed, hydroxylamine derivatives, which activate optic atrophy-1 and promote the fusion of inner mitochondrial membranes, ameliorated lung damage in a murine model of pulmonary arterial hypertension [51]. Recently, treatment with a drug that prevents activation of the mitochondrial fission marker dynamin related protein (DRP)-1 ameliorated vascular remodeling and inflammation in spontaneously hypertensive rats [52], in accordance with previous observations in cardiomyocytes subjected to renal [53] and cardiac [54] reperfusion injury.…”
Section: Mechanisms Of Mitoprotectionsupporting
confidence: 75%
“…Manipulation of mitochondrial dynamics is a new strategy to decrease cardiac injury during ischemia-reperfusion. 197, 198 Thus, the enhanced oxidant production present in the aged heart may impair protective mitochondria fission-based responses to superimposed disease. Modulation of mitochondrial dynamic changes may be a strategy to attenuate the deleterious impact of age-related defects in the ETC.…”
Section: Mitochondrial Fission and Fusionmentioning
confidence: 99%
“…Another interesting example is the work by Sumida et al [229] where they showed that mouse kidney subjected to acute IRI induced mitochondrial fragmentation in the heart, resulting in apoptosis and cardiac dysfunction, the effects of which could be reverse by pharmacological inhibition of Drp1 using mdivi-1 .…”
Section: Mitochondrial Fusion and Fission Proteins In Cardiac Healthmentioning
confidence: 99%